Relationship between spatio-temporal evolution of soil pH and geological environment/surface cover in the eastern Nenjiang River Basin of Northeast China during the past 30 years - Guo-dong Liu; Ming-hui Wei; Ze Yang; Hong-ye Xiao; Yi-he Zhang; Na-na Fang (China Geology)
ABSTRACT: To illuminate the spatio-temporal variation characteristics and geochemical driving mechanism of soil pH in the Nenjiang River Basin, the National Multi-objective Regional Geochemical Survey data of topsoil, the Second National Soil Survey data and Normalized Difference Vegetation Index (NDVI) were analyzed. The areas of neutral and alkaline soil decreased by 21100 km2 and 30500 km2, respectively, while that of strongly alkaline, extremely alkaline, and strongly acidic soil increased by 19600 km2, 18200 km2, and 15500 km2, respectively, during the past 30 years. NDVI decreased with the increase of soil pH when soil pH > 8.0, and it was reversed when soil pH < 5.0. There were significant differences in soil pH with various surface cover types, which showed an ascending order: Arbor < reed < maize < rice < high and medium-covered meadow < low-covered meadow < Puccinellia. The weathering products of minerals rich in K2O, Na2O, CaO, and MgO entered into the low plain and were enriched in different parts by water transportation and lake deposition, while Fe and Al remained in the low hilly areas, which was the geochemical driving mechanism. The results of this study will provide scientific basis for making scientific and rational decisions on soil acidification and salinization.©2023 China Geology Editorial Office.